Growth behaviour of anodic oxide film on titanium alloy. (1st November 2014) - Wu, L.; Liu, J. H.; Wu, G. L.; Li, S. M.; Yu, M.
Abstract : The growth behaviour of anodic oxide film on titanium alloy in a near neutral electrolyte (C4 H4 O6 Na2 ) under pulse galvanostatic method was investigated by scanning electron microscope, energy dispersive spectroscopy, X-ray photoelectron spectroscopy, atomic force microscopy and transmission electron microscopy (TEM). The morphology and roughness of the anodic oxide film were strongly dependent on the anodising time. The result of TEM showed that the oxide film was partly crystallised and mainly composed of amorphous TiO2 . The probable mechanism of film formation had been discussed, which was comprised of three distinctive stages. The growth behaviour of the anodic oxide film was not only vertical but also horizontal. The process of growth was nucleation, agglomeration and coagulation.